Diary of a wimpy kid. No brainer - Kinney, Jeff (New York Amulet Books, 2023)
"In No Brainer, it's up to Greg to save his crumbling school before it s shuttered for good. Up until now, middle school hasn't exactly been a joyride for Greg Heffley. So when the town threatens to close the crumbling building, he's not too broken up about it. But when Greg realizes this means he's going to be sent to a different school than his best friend, Rowley Jefferson, he changes his tune. Can Greg and his classmates save their school before it's shuttered for good? Or is this the start of a whole new chapter for Greg?" --
Accelerated Reader AR
Keywords: Heffley, Greg -- Juvenile fiction; Best friends -- Juvenile fiction; Protest movements -- Juvenile fiction; Student movements -- Juvenile fiction; Middle schools -- Juvenile fiction; Diaries -- Juvenile fiction; Humorous fiction; Diary fiction; School fiction